Expression profile of the SOX9 gene in the testes of sexually immature and mature male goats (Capra hircus), and its potential influence on postnatal testis development - I. Szatkowska; M. Jedrzejczak-Silicka; A. Dybus; B. Wiszniewska; J. Udala; D. Zaborski; J. Wojcik; T. Stankiewicz; W.S. Proskura (Veterinární Medicína, 2017)
The aim of this study was to compare the expression levels of the SOX9 (SRY-box 9) gene in the testes of 18 White improved male goats (Capra hircus) divided into three age groups (one, 10 and 15 months of age with seven, eight and three individuals per group, respectively). Abnormalities in testis development were observed in three individuals from the group of 10-month-olds. Additionally, differences in SOX9 expression that may affect the process of testis maturation and testicular spermatogenic activity were investigated among individuals. The expression of the SOX9 gene in testicular tissues was analysed using qPCR. Maximal SOX9 expression was observed in 10-month-old males with normal testes, while expression was significantly reduced in the same age group of males with abnormal testes. Abnormalities in testis development were associated with low parameters of semen quality. The lowest expression levels of SOX9 were observed in 15-month-old goats. The results of the present study indicate that SOX9 expression changes significantly during the development of male goats.